Evaluation of general anaesthesia by using Propionylpromazine, Xylazine and Ketamine in rabbits: M. J. Eesa ;R. A. Omar ,H. H. Mohammad Nazhat - Eesa, M. J. (The Iraqi Journal of Veterinary Medicine, 2012)
Safe and effective anaesthetic regimens have been described for use in rabbits,partially because of the susceptibility of this species to fatal respiratory arrest. Thepresent study was conducted to evaluate the efficacy of anesthetics, analgesicscombinations an anesthesia in twenty five local breed rabbits. Rabbits were injectedintramuscularly by: Propionylpromazine 0.5mg/kg B.W. as premedictation, after10minutes later Xylazine and Ketamine Hydrochloride at a dose of 20mg/kg,50mg/kg respectively. The results of the physiological parameters of the controlgroup at the period of zero time concerning rectal body temperature, respiratory rate,heart rate were 38.00±0.29 ºC; 96.36 ±3.33bpm; and 147.20±6.46/minutesrespectively. While in treated group at the periods 10, 20, 35, 50, 65, 80 and 95minutes were 37.76 ±0.61; 37.34± 0.28; 37.00± 0.29; 37.00±0.35; 36.92±0.38;35.80±0.40; 34.92± 0.53 ºC; 96.36±3.33; 41.00±1.37; 45.00±2.01; 45±2.01;40.00±1.31; 40.00±1.31; 39.20±1.01 bpm; and 147.20±6.46; 142.00±3.73;145.00±3.26; 144.48±3.31; 130.00±4.18; 140.00±3.49; 138.68 ±2.93 beats/minutes.The results of biochemical tests: Glucose, ALP, GPT, GOT in control group (zerotime) were: (137.40±1.97 mg/dl; 53.09±2.13 U/L; 51.48±4.31 U/L; 116.9±09.82U/L) respectively. And in treated group at the periods (10, 20, 35, 50, 65, 95 minutesand 24 hours) respectively were 139.60±0.79; 207.60±5.00; 222.20±7.42;359.20;±18.89; 341.60±15.30; 337.7±76.39 and 199.92±9.14 mg/dl; 39.74±2.74;42.55±3.29; 39.65±4.13; 42.48±2.62; 56.56±2.16; 47.41±3.61 and 42.84±4.16 U/L;46.17±3.92 ; 39.34±3.01; 44.69±3.05; 49.98±3.16; 51.65±4.03; 47.22±2.54 and72.63±4.98 U/L, and 94.72±8.24; 86.22±5.59; 90.82±6.89; 76.65±4.12; 82.70±4.69;100.6±7.39 and 126.6±7.77 U/L. The conclusion of this study investigate that thelose of righting reflex was 4.760±0.421 minutes; induction time was 8.44±1.05, thetime to complete muscle relaxation was 3.920±0.321 minutes, surgical time41.48±2.11 minutes, and recovery time was 45.76±2.43 minutes; in which thesurgical period was enough for the most of surgical interference, while the recoveryperiod was smooth and short in comparison with another anaesthetic regimen